Microstructure and mechanical properties of CuNiMo austempered ductile iron - Erić Olivera; Jovanović Marina P.; Šiđanin Leposava P.; Rajnović Dragan M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Microstructure and mechanical properties of Cu, Ni and Mo alloyed cast ductile iron have been investigated after austempering. Samples were austenitised at 860oC for 1h and then austempered at 320oC and 400oC in the interval from 0,5 to 5h. The X-ray diffraction technique and the light microscopy were utilized to investigate the bainitic transformation, while tensile and impact tests were performed for characterization of mechanical properties. By austempering at 320oC in the range between 2 and 5h, a microstructure typical for austempered ductile iron was produced, i.e. a mixture of free bainitic ferrite and highly carbon enriched retained austenite. The characteristic of the whole range of austempering at 400oC is the appearance of martensitic structure. The maximum impact energy (133 J) coincides with the maximum value of volume fraction of retained austenite that was obtained after 2,5h of austempering at 320oC. The appearance of martensite during austempering at 400oC is the main cause for much lower tensile properties than at 320oC.